Struktur kepribadian tokoh utama dalam kumpulan cerkak Langit Biru Kanaya karya Sunaryata Soemardjo - Putri, Egie Yuandita Syah; Widagdo, Sungging (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
A person's mental health affects their well-being, and a balanced personality structure between id, ego, and superego allows the main character to achieve their well-being. This is illustrated in Sunaryata Soemardjo's collection of cerkak Langit Biru Kanaya. The author displays the character's personality structure to deal with conflicts, so they can achieve prosperity. This study uses a descriptive qualitative method to analyze the main character's personality structure in Soemardjo's cerkak Langit Biru Kanaya, as described by Sigmund Freud's psychoanalysis theory. The data are in the form of words and sentences that contain the personality structure. The data source is Soemardjo's collection. This research found 75 data points of the main character's personality structure from 11 stories: 27 id, 24 ego, 24 superego. The id is the dominant personality structure, affecting the main character's welfare, which ends with regret due to impulsive decisions. The main character's personality structure in dealing with conflicts provides an illustration of resilience in facing problems and maintaining readers' mental health.